A new approach to calculate the nodule density of ductile cast iron graphite using a Level Set. (July 2016) - Rebouças, Elizângela S.; Braga, Alan M.; Marques, Regis C.P.; Rebouças Filho, Pedro Pedrosa
Highlights: New segmentation methodology of graphite nodules in nodular cast iron using Level Set method. New approach for calculation of the automatic graphite nodules densities using Level Set. Comparison of the method and the proposed approach with Digital Imaging Processing methods already applied for this purpose. The proposed approach is superior to others when compared by the experts in the field. Abstract: This paper proposes a new approach with digital image processing techniques to determine the number of graphite nodules on samples of nodular cast iron by following the NBR 6913 standard. Counting errors and excessive inspection time are common problems if the procedure is performed without the assistance of computational systems. To overcome these drawbacks, we propose here an algorithm for graphite nodule segmentation based on the Level Set technique. The proposed approach and two other computational methods, Watershed and Region Growing, are compared with the results given by experts using optical microscopy (OM). The results of the proposed method were closer to those of the experts using OM than the other two computational methods. The proposed method presented greater accuracy and faster execution time than the traditional method by visual inspection.